The Effect of Innovation and Fintech (Financing Access) On Repurchase Intention In Msmes Kampung Baru Village: Pengaruh Inovasi dan Fintech (Akses Pembiayaan) terhadap Repurchase intention pada UMKM di Kelurahan Kampung Baru - Angeline Hartono; Dedy Lazuardi (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to investigate the influence of innovation and fintech on the repurchase intention of culinary MSME consumers in Kampung Baru Village, Medan, which has been facing challenges of low product diversification, conventional capital constraints, and limited digital infrastructure. The descriptive quantitative method was applied by collecting data through questionnaires to 100 respondents who were selected incidentally and data analysis using SPSS 25 involving tests of validity, reliability, normality, multicollinearity, and multiple linear regression. The results of the study show that innovation has a positive and significant influence. Meanwhile, fintech also has a positive and significant effect on repurchase intention, with a determination coefficient of R² of 0.533 which means that the two variables explain 53.3% of the repurchase intention variable. These findings confirm the importance of synergy between innovation and fintech in increasing the repurchase intention of culinary MSMEs in Medan. Therefore, it is recommended that MSME actors conduct periodic market research, develop innovations according to consumer needs, and implement a simple digital recording system, fintech providers simplify the application interface, offer flexible loan tenors, and financial literacy modules.